Protype implementation of information server for seamless network handover over IPTV application - Mohamed R.R.; Hashim W.; Sameon S.S. (Penerbit UTM Press, 2023)
The use of mobile phone increases exponentially in our daily activities because it is light, mobile and handy that can be used anytime and anywhere. Checking emails, updating our daily status and diary, reading the latest news and online purchasing requires continuous network connection as well as a battery that can last. But sometimes the performance of internet speed is too weak where users are experiencing some problems and eventually leads to network disruption. Hence, users should be given the option to choose the internet connection or internet service provider that offer better service at that time moreover during an emergency. In this paper, we propose a development of Information Server to provide information to consumers about the available network surrounding within a reasonable time upon requested. This method is applied in the user terminal to allow the user freedom to decode on the best network handover. 2015 Penerbit UTM Press. All rights reserved.